Can María speak?: Interpreting Ixcanul/Volcano (2015) from a decolonial perspective - Alfaro Córdoba, Amanda (2018)
This article explores, describes and analyses the material, linguistic and cultural framework in which the central conflict in Ixcanul/Volcano (Bustamante, 2015) and its mise-en-scène operate, considering the film as an example of an intertextual practice that succeeds in connecting oral and dramatic traditions to a filmic register. By analysing how the film aims to be realistic and locate itself within a contemporary Guatemalan context, this study argues that, due to the film’s political intentions, themes and intended audience, Ixcanul challenges several power structures that preclude decolonial dialogue in the country. Furthermore, by describing how the subaltern subject, María, endures and resists strategies of invisibilization, I read Ixcanul in light of analytical tools drawn from postcolonial and decolonial frameworks to disentangle the structures of domination – the coloniality of power – represented in the film.